Ambulatories and Chapels in the Churches of Thessaloniki of the 8th–12th Centuries: The Main Approaches to the Research - Freze, Anna A. (Actual Problems of Theory and History of Art, 2022)
In the Middle Byzantine period, several chapels were introduced into the complexes of the Early Byzantine basilicas of Thessaloniki, the Church of Hagios Demetrios and the Church of Theotokos Acheiropiitos. Two eastern chapels and probably corresponding flanking ambulatories were erected in the 10th century for the katholikon of John the Forerunner monastery. The katholikon of the St. Theodosia (?) monastery had a southern ambulatory likely ending with a parekklesion. During this period two chapels may have been built at the northern façade of the Cathedral of St. Sophia. However, the accumulated archaeological data do not allow to obtain a definite concept of the tradition of building ambulatories and chapels in Middle Byzantine Thessaloniki. The archaeological studies of the majority of the monuments are not complete and their datings range within several centuries. Though the available evidence testifies to significant importance of the periphery in the contemporary church architecture. To continue the research the chapels and ambulatories in Thessaloniki should be studied in the context of parallel building practice in Constantinople, as well as in the Macedonian lands as a whole. Dating, construction specifics, and functions of the annexes to the St. Sophia cathedral in Thessaloniki are very important issues to study.This research was funded by the Russian Scientific Fund, project 20-18-00294 “Artistic Traditions and Ecclesiastic-Political Ideology in the Medieval Architecture and Art of the Balkans. Macedonian question”.
Keywords: Thessaloniki; Byzantine architecture; ambulatories; chapels; church architecture